Development of high-performance electric machine for electric vehicles - Kow, Benedict Wei Jie (Nanyang Technological University, 2020)
As electric vehicles (EVs) and hybrid electric vehicles (HEVs) are starting to gain traction in the recent years, focus have been shifted to developing a more efficient and versatile electric drive for such vehicles. Direct current (DC) drives are one of the widely used in EVs due to them possessing the advantage of simple control. However, one of the main problems of DC drives are the use of commutators and brushes, which causes the drives to be less dependable and unfit for operations that require little to no maintenance.[1] Thus, this final year project (FYP) would focus on the development of high-performance permanent-magnetelectric machine for EVs and HEVs, using JMAG to analyse its mathematical model to determine if the drive is suitable for the vehicle’s intended operation.